2016
DOI: 10.1134/s0016793216070082
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of sunspot longitudinal distribution and their correlation with solar activity in pre-Greenwich data

Abstract: We study and compare characteristics of sunspot group latitude distribution in two catalogs: the extended Greenwich (1874-2014) and Schwabe ones (1825-1867) [1]. We demonstrate that both datasets reveal similar links between latitude and amplitude characteristics of the 11-year cycle: the latitude dispersion correlates with the current activity and the mean latitude of sunspots in the cycle's maximum is proportional to its amplitude, It agrees with conclusions that we made in papers [2, 3] for the Greenwich ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…These values indicate that the spot size increases with increasing latitude. This tendency is similar to the sunspot property that the cycleintegrated sunspot area is positively correlated with the mean latitude Solanki et al 2008;Ivanov & Miletsky 2016). Although the A-type binaries also show a similar association at least below λ ∼ 60 • (rp = −0.415 with p = 0.110 and rs = −0.356 with p = 0.175 in the range 30 • < θ < 90 • , and rp =0.334 with p = 0.191 and rs =0.430 with p = 0.085 in the range 90 • < θ < 150 • ), these correlations are weaker than those of the W-type sample.…”
Section: Positionsupporting
confidence: 73%
“…These values indicate that the spot size increases with increasing latitude. This tendency is similar to the sunspot property that the cycleintegrated sunspot area is positively correlated with the mean latitude Solanki et al 2008;Ivanov & Miletsky 2016). Although the A-type binaries also show a similar association at least below λ ∼ 60 • (rp = −0.415 with p = 0.110 and rs = −0.356 with p = 0.175 in the range 30 • < θ < 90 • , and rp =0.334 with p = 0.191 and rs =0.430 with p = 0.085 in the range 90 • < θ < 150 • ), these correlations are weaker than those of the W-type sample.…”
Section: Positionsupporting
confidence: 73%
“…Finally, Solanki et al (2008) have computed various moments of sunspot distribution, separately for two hemispheres, and have shown that the three lowest moments (i.e, the total area covered by the sunspots over a cycle, the mean sunspot latitudes, and the width of the distribution) are well correlated with each other. Recently, Ivanov & Miletsky (2016) showed that the latitude properties of sunspot distribution are much more stable against the gaps of observations and hence these properties can be used for estimates of quality of observations and for data series calibration.…”
Section: Introductionmentioning
confidence: 99%
“…These sources include information not only on numbers, but also on heliolatitudes of sunspots. As we showed in [3,4], there is a high correlation between the latitude dispersions of sunspots and power of solar activity. Therefore, we can made independent estimates of the activity level in this epoch.…”
Section: Introductionmentioning
confidence: 59%
“…
Two important sources of information about sunspots in the Maunder minimum are the Spörer catalog [1] and observations of the Paris observatory [2], which cover in total the last quarter of the 17th and the first two decades of the 18th century.These data, in particular, contain information about sunspot latitudes. As we showed in [3,4], dispersions of sunspot latitude distributions are tightly related to sunspot indices, so we can estimate the level of solar activity in this epoch by a method which is not based on direct calculation of sunspots and is weakly affected by loss of observational data.The latitude distributions of sunspots in the time of transition from the Maunder minimum to the common regime of solar activity proved to be wide enough. It gives evidences in favor of, first, not very low cycle No.
…”
mentioning
confidence: 99%
See 1 more Smart Citation